Shakespeare dancing : - Brown, John Russell (Palgrave Macmillan, 2005)
In his newest book, noted Shakespeare and theater scholar John Russell Brown explores the operation of the playwright's creative mind in his most frequently performed texts and encourages readers to seek out the performance possibilities of the works for themselves. Moving beyond the study of what has happened on stage in a number of specific productions, Brown examines the entire theatrical event in which performance occurs, as well as the meeting and interaction of actors and audience, and the social and cultural contexts of the plays' reception in the past and present.